Age and gender variations of sleep in subjects without sleep disorders. (18th August 2015) - Luca, Gianina; Haba Rubio, José; Andries, Daniela; Tobback, Nadia; Vollenweider, Peter; Waeber, Gérard; Marques Vidal, Pedro; Preisig, Martin; Heinzer, Raphaël; Tafti, Mehdi
Abstract : Objective. Although sleep is a biomarker for general health and pathological conditions, its changes across age and gender are poorly understood. Methods. Subjective evaluation of sleep was assessed by questionnaires in 5, 064 subjects, and 2, 966 were considered without sleep disorders. Objective evaluation was performed by polysomnography in 2, 160 subjects, and 1, 147 were considered without sleep disorders. Only subjects without sleep disorders were included (aged 40–80 years). Results. Aging was strongly associated with morning preference. Older subjects, especially women, complained less about sleepiness, and pathological sleepiness was significantly lower than in younger subjects. Self-reported sleep quality and daytime functioning improved with aging. Sleep latency increased with age in women, while sleep efficiency decreased with age in both genders. Deep slow-wave sleep decreased with age, but men were more affected. Spectral power densities within slow waves (< 5 Hz) and fast spindles (14–14.75 Hz) decreased, while theta-alpha (5-1 Hz) and beta (16.75–25 Hz) power in non-rapid eye movement sleep increased with aging. In REM sleep, aging was associated with a progressive decrease in delta (1.25–4.5 Hz) and increase in higher frequencies. Conclusions. Our findings indicate that sleep complaints should not be viewed as part of normal aging but should prompt the identification of underlying causes.